MOF-derived crumpled-sheet-assembled perforated carbon cuboids as highly effective cathode active materials for ultra-high energy density Li-ion hybrid electrochemical capacitors (Li-HECs) - Banerjee, Abhik; Upadhyay, Kush Kumar; Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Nanoscale, 2014)
Lithium ion hybrid capacitors (Li-HECs) have attracted significant attention for use in next generation advanced energy storage technologies to satisfy the demand of both high power density as well as energy density. Herein we demonstrate the use of very high surface area 3D carbon cuboids synthesized from a metal-organic framework (MOF) as a cathode material with Li4Ti5O12 as the anode for high performance Li-HECs. The energy density of the cell is similar to 65 W h kg(-1) which is significantly higher than that achievable with commercially available activated carbon (similar to 36 W h kg(-1)) and a symmetric supercapacitor based on the same MOF-derived carbon (MOF-DC similar to 20 W h kg(-1)). The MOF-DC/Li4Ti5O12 Li-HEC assembly also shows good cyclic performance with similar to 82% of the initial value (similar to 25 W h kg(-1)) retained after 10 000 galvanostatic cycles under high rate cyclic conditions. This result clearly indicates that MOF-DC is a very promising candidate for future P-HEVs in a Li-HEC configuration.